EUFEMISME PENERJEMAHAN UNGKAPAN SEKSUAL NOVEL “SEPERTI DENDAM, RINDU HARUS DIBAYAR TUNTAS” KE DALAM BAHASA INGGRIS - Putri Sutaji, Tirta Ningtyas Alifia; Suray Agung Nugroho (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Euphemisms are often used in literary works The study aims to analyze the euphemistic form of sexuality expression in the translation of Eka Kurniawan's novel "Like Dendam, Rindu Must Be Paid Completely" into English and the factors of the euphemism. This research uses qualitative methods with a descriptive approach. The theory used is the euphemism theory of Allan and Burridge. The results of this study found 40 data on sexuality expressions divided into three categories, namely sexuality expressions that refer to physiological, sexual activity, and social life. The expression of sexuality that refers to a view of social life is the main finding in this study. In the three categories of sexuality expressions, 5 categories of euphemisms were found, namely part for whole, general for specific, remodeling, filipancy, and Omission. Cultural differences and the absence of matching words are the main factors in the euphemism in the translation of the novel.